Citizen science towards the regulation of medical cannabis in Argentina - Óscar Aguilar; María Cecilia Díaz; Lucía Romero (Tapuya, 2022)
In this paper, we discuss the meanings assumed by citizen science for the regulation of therapeutic and medical uses of cannabis in Argentina, considering the mobilization of experiences in three municipalities of the province of Buenos Aires. Through conceptual tools of the STS field and techniques such as documentary analysis of resolutions and ordinances, participant observation, and in-depth interviews, we address the role of proximity experienced locally in the development of municipal regulation initiatives; the combination of different types of expertise (technical, scientific, medical, legal, experiential); and the processes of resignification and change of social identifications. The research shows that local regulations emerge from a heterogeneous social base that, in the form of citizen science, produces, uses, and transmits diverse expertise around the therapeutic uses of the plant and its derivatives. It also reveals that the construction processes of local government policies promote new social perceptions of certain groups (supportive growers, physicians, child users) that influence the way that therapeutic cannabis is settled as a public problem.